Effects in mechanical properties and structure of the soil after tillage with rotary paraplow - Albiero, D.; Maciel, Antonio José da Silva; Monteiro, Leonardo de Almeida; Lanças, Kléber Pereira [UNESP]; Gamero, Carlos Antonio; Melo, R. P.; Araújo, M. C. (My University, 2014)
At present great emphasis is being put on soil preparation tools which conserve the initial conditions of soil structure, preventing erosion and preserving soil for future generations. A new conservational tillage tool – the rotary paraplow, it were carried out studies addressing the changes in structure and in mechanical properties of soil after tool operation. Dimensional analysis has been used as methodology since it calls for a judicious choice of dependent and independent variables of the studied phenomenon, followed by a method of algebraic calculation used to determine the components and essential combinations among the parameters, reaching the determination of the minimum number of repetitions. The results have shown that Rotary Paraplow generated a well-prepared subsurface cultivation furrow. The evaluation of the operational tests for the dimensionless graphs has determined that the best setting is that in which the tool works with forward speed of 0.36 m.s-1, rotation of 514 min-1 and depth of 150 mm. The action of this new tool can be considered as conservation tillage because all parameters are within limits imposed by the literature on the subject in order to consider soil tillage as conservational.
Keywords: Soil dynamics; Dimensional analysis; Paraplow